Endovascular repair of aneurysms of the abdominal aorta: patients with hostile anatomy of the aneurysm neck - Kalmykov, E. L.; Droc, I.; Kheladze, G.; Suchkov, I. A.; Dammrau, R. (Frontiers in Surgery, 2025)
IntroductionIn some cases, endovascular abdominal aortic repair (EVAR) may be hampered by specific anatomical features, the so-called “hostile neck.”AimTo analyse the results after implanting Gore excluder conformable endograft prostheses in patients with hostile neck anatomy who had experienced an infrarenal aneurysm.MethodsThis is a retrospective, multicentre study that included 30 patients who were treated between April 2019 and August 2023. Primary endpoints were technical success, immediate results with intraoperative mortality and rate of endoleaks, short-term results with 30-day mortality, complications, endoleaks, migration rate, and mid-term follow-up.ResultsEVAR was performed in 29 (96%) patients as an elective surgery and in one patient as emergency treatment. The median age of the patients was 75.0 years (range 71.0–79.0); of them, 83.3% were men. The median diameter of the aneurysm was 58.5 mm (range 55.0–66.0 mm). The median angle of the neck of the aortic aneurysm was 80.0° (range 30.0–90.0), with a median length of 15.0 mm (range 10.0–21.0). Of the 30 patients, seven fell outside the standard instructions for use. The technical success rate of the procedure was 100%. In three patients, one of the renal arteries was stented using the chimney technique. No type Ia or Ib endoleak was detected intraoperatively. In one patient, acute thrombosis of the graft was diagnosed after 21 days, requiring graft explantation. The 30-day mortality rate was 3.3%. No endoleaks of types Ia or Ib were identified before discharge from hospital. An endoleak of type II was identified in four patients. No local complications were identified. The mean follow-up period was 25.5 months (range 6.0–36 months). No further intervention was required. No late aortic rupture, endoprosthesis migration, or death was subsequently observed.ConclusionThe use of Gore excluder conformable endoprostheses is an effective method to treat abdominal aortic aneurysms with hostile neck, with good mid-term results; however, further research on long-term results is necessary.